Analysis of Factors Influencing Mental Health in Adolescents: Literature Review - Ramdani, Ubaidillah; Azari, Abdul Aziz (Jurnal Keperawatan Jiwa, 2024)
Adolescence is a period of rapid growth and development, both physically, psychologically, and intellectually. Adolescents have great curiosity, like adventure and challenges, and dare to make decisions without careful consideration. If the decision is not correct, it can risk causing various physical and psychosocial health problems. This literature review aims to determine the factors influencing adolescent mental health. The data for this study were taken from four relevant databases, PubMed, Science Direct, EBSCO, and Google Scholar, using the PIOS (Participant, Intervention, Outcomes, and Study Design) method and MeSH terms on the search engine. The keywords "behavior" or "behavior," "mental health," "mental health," and "teenager.” The data were from journals published in 2020-2024 in English and Indonesian (open access and full text) and original articles. Of the n = 3,252 articles found, only n = 10 met the inclusion criteria. The results of this literature review explain that several factors are considered to influence mental health, namely gratitude, parenting patterns, knowledge, intensity of social media use, bullying, and family roles. Identifying these factors is very important in formulating more comprehensive nursing interventions.